Evaluation of C18 monolithic columns for radiochemical purity measurement. (13th July 2016) - Schenk, David J.; Welch, Christopher J.; Antonucci, Vincent
Abstract : Speeding the analysis of reaction aliquots, high‐performance liquid chromatography (HPLC) fractions and final products continue to be an area of great interest in the study of radiopharmaceuticals. Translating recently developed rapid HPLC and ultra high‐performance liquid chromatography analysis approaches to radio‐HPLC can sometimes be fraught with peril, owing to specific peculiarities of online radiochemical chromatographic detection (notably, a proportionally large system volume for the radio‐HPLC detector). In this study, we investigate an alternate approach for rapid radio‐HPLC analysis where a 150‐cm C18 monolithic column is used with a 15‐min run time. To ascertain this method's ability to distinguish between radiolabeled compounds with acceptable (≥97%) and unacceptable purity, the results were compared with results from a conventional HPLC 45‐min method using a 25‐cm C18 column, where a large radiodetector cell volume is of lower impact. Overall, for the 54 radiolabeled compounds assayed by the two methods, there were similar measured radiochemical purities, but cases were also found where there were significantly large differences between the results (>1%). A calculated confidence of 85% was found for the 15‐min monolithic method's ability to accurately reproduce the corresponding result from the 25‐cm column method. Abstract : The performance of a C18 monolithic column was evaluated by comparing its radiochemical results with those from a traditional 25‐cm C18 column. Most results were similar for the 54 compounds assayed, but a few cases with large differences (>1%) were found. A confidence of 85% was calculated for the 15‐min monolithic method's ability to reproduce the conventional column result.